Leukapheresis in non–cytokine‐stimulated donors with a new apheresis system: first‐time collection results and evaluation of subsequent cryopreservation. Issue 4 (15th July 2012) - Steininger, Philipp A.; Smith, Richard; Geier, Christoph; Zimmermann, Robert; Eckstein, Reinhold; Strasser, Erwin F.
<x xml:space="preserve">Abstract</x> BACKGROUND: Adoptive cell therapy based on mononuclear cells (MNCs) became an important modality of cancer immunotherapy. Data about collection results and donor response of leukapheresis with the Spectra Optia v.5.0 (Terumo BCT) in nonmobilized donors are required. STUDY DESIGN AND METHODS: Twelve MNC collections were performed using the Spectra Optia v.5.0 in non–cytokine‐stimulated donors. Leukapheresis products and peripheral blood samples from donors were assayed for CD45+, CD34+, CD3+, and CD14+ cells by flow cytometry. Prefreeze and postthaw cell counts, cell viability, and numbers of colony‐forming units were assessed in cryobags and compared to data from cryovials. RESULTS: Leukapheresis yielded a mean of 5.26 × 109 ± 2.2 × 109 CD45+ cells, 1.5 × 109 ± 0.77 × 109 CD14+ monocytes, and 2.28 × 109 ± 1.2 × 109 CD3+ T cells by processing 6690 ± 930 mL of whole blood. A significant positive correlation between yield of CD3+ T cells and residual platelets (PLTs) and red blood cells (RBCs) was observed. This did not apply for CD34+ and CD14+ white blood cell subsets. Mean collection efficiencies for CD14+ monocytes and CD3+ T cells were 61.8 ± 17 and 37.2 ± 18%, respectively. Recovery of CD14+ cells after cryopreservation was 75.2 ± 8.2%, which was significantly lower than recovery of CD45+ cells (81.4 ± 5.5%; p = 0.01). CONCLUSION: This study of a small cohort demonstrates that the Spectra Optia v.5.0 is capable of collecting low product volumes with satisfactory MNC yields and low residual RBCs and PLTs in non–cytokine‐mobilized apheresis. Our data suggest that cryovials can serve as a representative surrogate for the primary product cryobag.